2013
DOI: 10.1016/j.rbr.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre variáveis demográficas e clínicas, e a gravidade da fibromialgia

Abstract: The impact of FM measured by the FIQ is directly correlated with the severity of depression and the presence of workers' compensation interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
2
2
1
5
Order By: Relevance
“…The comparison of mean pain intensity before and after the intervention showed a significant reduction in pain (from 5.4 to 4.3). The mean pain intensity observed in this study was lower than in other studies, which found a mean pain around eight 7,9 at the Outpatient Rheumatology Clinic of the Federal University of Paraná (UFPR) and at the Rheumatology Service of the University Hospital of Recife 10,11 . With regard to depressive symptoms, the reduction of the mean depression score after the nursing intervention was not significant (p = 0.093).…”
Section: Discussioncontrasting
confidence: 89%
“…The comparison of mean pain intensity before and after the intervention showed a significant reduction in pain (from 5.4 to 4.3). The mean pain intensity observed in this study was lower than in other studies, which found a mean pain around eight 7,9 at the Outpatient Rheumatology Clinic of the Federal University of Paraná (UFPR) and at the Rheumatology Service of the University Hospital of Recife 10,11 . With regard to depressive symptoms, the reduction of the mean depression score after the nursing intervention was not significant (p = 0.093).…”
Section: Discussioncontrasting
confidence: 89%
“…The above reconfirms the data obtained in many other studies, which establish TAG as an active comorbidity in people with FM. The above agrees with the findings of authors such as Alok, Weir and Martínez (Alok, Das, Agarwal, Salwahan, & Srivastava, 2010;Martinez, de Melo Casagrande, Ferreira, & Rossatto, 2013;Weir et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…O critério utilizado para determinar o tamanho da amostra foi a saturação de dados, ou seja, fechamento amostral quando os dados obtidos passaram a apresentar repetição, na avaliação dos pesquisadores e considerando o referencial dos Itinerários Terapêuticos 4 . O espaço amostral alcançou o número de 15 entrevistas, quantidade coincidente com a do estudo qualitativo de Martinez et al 5 Os critérios de inclusão foram pessoas com: (a) idade igual ou superior a 18 anos; (b) diagnóstico confirmado de fibromialgia, de acordo com os critérios propostos pelo Colégio Americano de Reumatologia, validados no Brasil 6 ; e (c) atendidas no Cendor.…”
Section: Métodosunclassified
“…As participantes parecem ter escolhido caminhos de itinerário terapêutico que faziam sentido para elas, ou seja, escolhas ancoradas em suas experiências anteriores, socialmente construídas 23 , marcando o início do seu contato com o sistema de saúde. O tempo decorrido entre os sintomas iniciais e o diagnóstico final foi longo, com média de tempo desde o início dos seus sintomas até o diagnóstico compatível com a literatura 5,24 . A dificuldade de chegar a um serviço de saúde de nível terciário também foi explanada em estudo realizado em São Paulo, Brasil, por Saltareli et al 2 que, além da demora em conseguir atendimento, também revelaram demora no encaminhamento para o serviço especializado de reabilitação.…”
Section: A Descoberta Do Diagnósticounclassified